Princetonians, 1776-1783 : a biographical dictionary - Harrison, Richard A., 1945- (Princeton University Press, 1981)
This volume, the third in a series of biographical sketches of students at the College of New Jersey (now Princeton University), is an account of the College and its alumni during the troubled years of the Revolution. Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions.
"Third volume in the series of biographical dictionaries of Princetonians"--Preface
Keywords: Princeton University -- Alumni and alumnae -- Biography.; Princeton University; BIOGRAPHY & AUTOBIOGRAPHY -- General.; Universities and colleges -- Alumni and alumnae; dictionaries.; Dictionaries; Biographies; Biographies.; Dictionaries.; Dictionnaires.